A precedence evaluation of demand and supply between vocational high school graduates and workforce requirement in Indonesia - Jaedun, Amat; Omar, Muhd Khaizer; Kartowagiran, Badrun; Istiyono, Edi (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
The success in implementing the demand-driven approach in Vocational High Schools (VHS) can be realized by understanding the misalignment between graduate skill competency and workforce demand by the industry. This study aims at describing the precedence between the VHS graduates and the businesses/industrial sector (BS/IS) portraying from the regional potential perspectives. The research data was collected from documents, and survey forms distributed to BS/IS within the research population. The document analysis was employed to collect information on programs offered at VHS, existing VHS student enrollment, and the value of Gross Regional Domestic Product (GRDP) in studied provinces. An online survey was distributed to all VHS graduates and BS/IS employers. The content validity was carried out prior actual study to ensure the validity of the instrument. A descriptive analysis was performed to gather information pertaining to developed research objectives. The precedence of the academic programs with the GRDP was determined based on 5% of criteria differences. The results found that there is a misalignment between the academic programs and the VHS student's enrollment towards the region job potentials in each province in Indonesia. In addition, the research also found that the competency of VHS graduates related to theoretical knowledge, job characteristics, and workforce skills were at a moderate level. The implication of the study offers a salient notion on minimizing the precedence that occurs between the supply and demand in the form of graduates supply to the workforce and, at the same time, fulfilling the workforce requirements demand by the industries.